USM VOLUNTEERS RETURN AFTER SUCCESSFUL MISSION IN KELANTAN - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
KOTA BHARU, 7 January 2015 Volunteers comprising staff from Universiti Sains Malaysia (USM) have successfully helped three schools in Kelantan by cleaning about 80 percent of the remaining mud and dirt that was left behind by the floods.